The Grüneisen parameter applied to critical phenomena and experimental investigations of correlated phenomena in molecular conductors - Squillante, Lucas Cesar Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Critical phenomena are of great interest to the scientific community and can be widely extended to various fields of research, such as classical and quantum phase transitions, caloric effects, and even Biology in brain functionality, for instance. As broadly discussed in the literature, the smoking-gun physical quantity to experimentally access both finite-temperature and quantum critical points is the so-called Grüineisen ratio. In this Ph.D. Thesis, a systematic review is performed on the derivation and generalization of the Grüneisen parameter followed by its unprecedented applications to several distinct scenarios, such as magnetic model systems, zero-field quantum phase transitions, the maximization of caloric effects close to any critical-end point based on entropy arguments, the here-proposed adiabatic magnetization of a paramagnetic salt, as well as for Cosmology in the frame of the universe expansion. Since this Ph.D. Thesis is a symbiosis between theoretical and experimental results, an experimental investigation of correlated phenomena was carried out for molecular conductors of the (TMTTF)2X family, where TMTTF is the base molecule tetramethyltetrathiafulvalene and X a monovalent counter- anion such as PF6, SbF6, or AsF6. Such strongly correlated electron systems are considered suitable ones for the exploration of Mott insulating phase, charge-ordering, spin-Peierls, and superconductivity. In particular, the investigation of a possible multiferroic character in these salts was performed via quasi-static (low-frequency) dielectric constant ε′ measurements as a function of temperature where a maximum in ε′ as a function of temperature was observed at the corresponding charge-ordering temperature for both hydrogenated and 97.5% deuterated (TMTTF)2SbF6 salts. Furthermore, Raman measurements were performed on the 97.5% deuterated (TMTTF)2PF6, showing a possible magneto-optical effect on the ν4(ag) vibrational mode of the TMTTF molecule. Yet, fluorescence measurements demonstrated that the fully-hydrogenated (TMTTF)2AsF6 presents an expressive fluorescence background, which is roughly five orders of magnitude lower than that for the 97.5% deuterated variant of (TMTTF)2PF6.

Fenômenos críticos são de grande interesse para a comunidade científica e podem ser estendidos para várias áreas de pesquisa, como transições de fase clássicas e quânticas, efeitos calóricos e até mesmo na Biologia no contexto da funcionalidade cerebral, por exemplo. É discutido amplamente na literatura que a grandeza física crucial para se acessar experimentalmente tanto pontos críticos a temperatura finita quanto pontos críticos quânticos é a chamada razão Grüneisen. Nesta tese de doutorado, uma revisão sistemática é realizada sobre a derivação e generalização do parâmetro de Grüneisen seguido pelas suas aplicações inéditas para diversos cenários físicos distintos, tais como sistemas modelo para o magnetismo, transições de fase quântica a campo magnético zero, a maximização de efeitos calóricos próximos de qualquer ponto crítico baseado em argumentos de entropia, para a magnetização adiabática de um sal paramagneto proposta nesta tese, bem como para a Cosmologia no contexto da expansão do universo. Uma vez que esta tese de doutorado é uma simbiose entre resultados experimentais e teóricos, uma investigação experimental de efeitos correlacionados em condutores moleculares também foi realizada para os condutores moleculares da família (TMTTF)2X, onde TMTTF é a molécula base tetrametiltetratiafulvaleno e X um contra-ânion monovalente, tais como PF6, SbF6 ou AsF6. Tais sistemas eletrônicos fortemente correlacionados são considerados apropriados para a exploração de isolantes de Mott, fase de carga ordenada, spin-Peierls e até mesmo supercondutividade. Em particular, uma investigação do possível caráter multiferroico destes sais foi realizada utilizando medidas de constante dielétrica quase estática (baixa frequência) ε′ em função da temperatura onde um máximo de ε′ foi observado na temperatura de ordenamento de carga correspondente para a variante totalmente hidrogenada e 97,5% deuterada do sal (TMTTF)2SbF6. Além disso, experimentos Raman foram realizados na variante 97,5% deuterada do sistema (TMTTF)2PF6, onde um possível efeito magneto-óptico no modo vibracional ν4(ag) da molécula TMTTF foi observado. Ainda, experimentos adicionais mostraram que o sistema totalmente hidrogenado (TMTTF)2AsF6 apresenta uma expressiva fluorescência, a qual é cerca de cinco ordens de magnitude maior do que a da variante 97,5% deuterada do sistema (TMTTF)2PF6.
O parâmetro de Grüneisen aplicado a fenômenos críticos e investigações experimentais de fenômenos correlacionados em condutores moleculares
Keywords: Fenômenos críticos; Parâmetro de Grüneisen; Sistemas eletrônicos fortemente correlacionados; Critical phenomena; Grüneisen parameter; Strongly correlated electron systems